Modulation of the inflammatory response to decellularized collagen matrix for cartilage regeneration - Gvaramia, David; Kern, Johann; Jakob, Yvonne; Tritschler, Hanna; Brenner, Rolf E.; Breiter, Roman; Kzhyshkowska, Julia; Rotter, Nicole (Journal of Biomedical Materials Research Part A, 2021)
Decellularized extracellular matrices (DECM) are among the most common types of materials used in tissue engineering due to their cell instructive properties, biodegradability, and accessibility. Particularly in cartilage, a natural collagen type II matrix can be a promising means to provide the necessary cues and support for chondrogenic stem and progenitor cells (CSPCs). However, efficient remodeling of the transplanted DECM is largely dependent on the host immune response, with macrophages playing the central role in orchestrating both inflammatory and regenerative processes. Here we assessed the reaction of human primary macrophages to the cartilage DECM. Our findings show that the xenogeneic collagen matrix can elicit a mixed response in human macrophages, whereby the inflammatory response (M1) and the activation of remodeling (M2) type of macrophages are both present. Additionally, we demonstrate the inhibitory effect of macrophage response on the migratory capacity of human CSPCs. We further show that the inflammatory reaction of macrophages to the cartilage DECM, as well as the resulting inhibitory effects on CSPC migration, can be attenuated by interleukin-4 (IL-4). Finally, we demonstrate that IL-4 can effectively bind the matrix, thereby modulating macrophage response by reducing the inflammatory reaction and inducing the M2 phenotype.
CRIS-Team WoS Importer:2022-01-07